Shari'a: Islamic law in the contemporary context - Feldman, Noah; Johnston, David L.; Arjomand, Saïd Amir; Krämer, Gudrun; Würth, Anna; Akhavi, Shahrough; Opwis, Felicitas; Amanat, Abbas; Mottahedeh, Roy (Stanford Univ. Press, 2007)
Griffel, Frank: Introduction. - S. 1-19 Krämer, Gudrun: Justice in modern Islamic thought. - S. 20-37 Griffel, Frank: The harmony of natural law and Shari'a in Islamist theology. - S. 38-61 Opwis, Felicitas: Islamic law and legal change: the concept of "maslaha" in classical and contemporary Islamic legal theory. - S. 62-82 Johnston, David L.: 'Allal al-Fasi: Shari'a as blueprint for righteous global citizenship? - S. 83-103 Feldman, Noah: Shari'a and Islamic democracy in the age of al-Jazeera. - S. 104-119 Amanat, Abbas: From "ijtihad" to "wilayat-i faqih": the evolution of the Shiite legal authority to political power. - S. 120-136 Akhavi, Shahrough: Shiite theories of social contract. - S. 137-155 Arjomand, Sai͏d Amir: Shari'a and constitution in Iran: a historical perspective. - S. 156-164 Würth, Anna: The normativity of the factual: on the everyday construction of Shari'a in a Yemeni family court. - S. 165-177 Mottahedeh, Roy P.: Afterword. - S. 178-181